Transcriptional profile changes after treatment of ischemia reperfusion injury-induced kidney fibrosis with 18β-glycyrrhetinic acid - Yamei Jiang; Chengzhe Cai; Pingbao Zhang; Yongsheng Luo; Jingjing Guo; Jiawei Li; Ruiming Rong; Yi Zhang; Tongyu Zhu (Renal Failure, 2022)
Introduction Chronic kidney disease (CKD) is characterized by renal fibrosis without effective therapy. 18β-Glycyrrhetinic acid (GA) is reported to have detoxification and anti-inflammatory functions and promotes tissue repair. However, the role of GA in CKD remains unclear. In this study, we investigated whether GA has a potential therapeutic effect in kidney fibrosis.Methods A renal fibrosis mouse model was established by ischemia/reperfusion (I/R) injury via clamping unilateral left renal pedicle for 45 min; then, the mice were treated with vehicle or GA. Kidney tissues and blood samples were extracted 14 days after reperfusion and renal function, histopathological staining, quantitative PCR, and western blotting were performed. RNA-seq was performed to explore the changes in the transcriptional profile after GA treatment.Results Renal function, pathological and molecular analysis displayed that fibrosis was successfully induced in the I/R model. In the GA treatment group, the severity of fibrosis gradually reduced with the best effect seen at a concentration of 25 mg kg −1. A total of 970 differentially expressed genes were identified. Pathway enrichment showed that reduced activation and migration of inflammatory cells and decreased chemokine interaction in significant pathways. Protein–protein interaction networks were constructed and 15 hub genes were selected by degree rank, including chemokines, such as C3, Ccl6, Ccr2, Ptafr, Timp1, and Pf4.Conclusions GA may alleviate renal fibrosis by inhibiting the inflammatory response. GA is a promising therapy that may perhaps be used in treating renal fibrosis and CKD.